LEGAL OBSCURITY SURROUNDING FOREIGN DIRECT INVESTMENT IN INDONESIAS DIGITAL SECTOR - Faizah, Farah (Student Journal of International Law, 2024)
This article examines the legal uncertainties surrounding the basis for Foreign Direct Investment (FDI) in Indonesias digital business sector. This research employs a normative-juridical approach, focusing on the analysis of existing laws, regulations, and legal precedents related to FDI in Indonesia's digital sector. We have reviewed legal texts, procedural guidelines, and relevant case studies to inform our findings. The primary legal issue addressed in this study is the lack of clarity in specific regulations governing FDI in digital businesses. This ambiguity has led to an increase in illegal investments, as foreign investors navigate a complex legal landscape with inadequate guidance. By highlighting these ambiguities, we seek to provide insights into how these legal uncertainties hinder legitimate investment opportunities and contribute to the proliferation of unauthorized investment activities. The findings indicate that the obscurity of regulations surrounding digital business FDI has created significant challenges for both investors and regulators. The lack of coherent and targeted legislation not only inhibits potential foreign investment but also increases the risks of non-compliance among investors. Moreover, the study reveals that existing laws often fail to account for the unique characteristics and rapid evolution of the digital landscape.